A new formula of Rotational Stiffness Coefficient of pile hinged on top under moment load. (November 2019) - Chen, Guozhou; Lin, Zhiyong; Lin, Wenbin
Abstract: The analysis and design of single piles subjected to lateral load are very important. The traditional expression for calculating rotational stiffness coefficient is too complex, and it needs large amount of computation. This paper proposes a new approach for getting rotational stiffness coefficient of pile hinged on top under moment load. It has been proved that the new method is the equivalent of traditional method of calculating rotational stiffness coefficient using power series. A case study shows that the same answer can be gotten in calculating rotational stiffness coefficient by the two methods. However, a large computational cost can be reduced by the new method.